Explicit Evidence of an Implicit Contract - Andrew T. Young; Daniel Levy (The Journal of Law, Economics, and Organization, 2014)
We offer the first direct evidence of an implicit contract in a goods market. The evidence comes from the market for Coca-Cola. Since implicit contracts are unobservable, we adopt a narrative approach to demonstrate that the Coca-Cola Company left a written evidence of the implicit contract with its customers—a very explicit form of an implicit contract. The implicit contract promised a 6.5oz Coca-Cola of a constant quality, the “secret formula,” at a constant price, 5. We show that Coca-Cola attributes and market structure made it a suitable candidate for an implicit contract. Focusing on the observable implications of such an implicit contract, we offer evidence of the Company both acknowledging and acting on this implicit contract, which was valued by consumers. During a period of 74 years, we find evidence of only a single case of true quality change. We demonstrate that the company perceived itself as vulnerable to consumer backlash by reneging on the pledge, and conclude that the perceived costs of breaking the implicit contract were large.
Keywords: E12; E31; K00; K12; K22; K23; L14; L16; L66; M21; M31; N80; A14; 330; Implicit Contract; Explicit Contract; Invisible Handshake; Customer Market; Long-Term Relationship; Price Rigidity; Sticky Prices; Price Adjustment; Quality Rigidity; Quality Adjustment; Nickel Coke; Coca-Cola; Secret Formula; Real Thing